Financial Integration, Investment, and Economic Growth: Evidence from Two Eras of Financial Globalization - Schularick, Moritz; Steger, Thomas M (The Review of Economics and Statistics, 2010)
Does international financial integration boost economic growth? The empirical literature has not yet established a robust link between openness to the international capital market and economic growth. In this paper, we turn to the economic history of the first era of financial globalization (1880–1914) for new insights. Using identical empirical models and techniques as contemporary studies, we find a significant growth effect in the historical period. A key difference between now and then is that opening up to the international market led to net capital movements and higher investment in the historical period, but it no longer does so today.